2003
DOI: 10.1002/eat.10170
|View full text |Cite
|
Sign up to set email alerts
|

Body image and eating disturbance among south Asian‐American women: The role of racial teasing

Abstract: Objective: Acculturation and loss of ethnic identification have been proposed as risk factors for eating and body image disturbance among women of color. This study investigated whether being teased about racial or ethnic features might also play a role in these disturbances in minority women. Methods: One hundred twenty-two college women of South Asian descent completed questionnaire measures of disturbed eating behavior, body image dissatisfaction, distress, self-esteem, acculturation, ethnic identification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(38 citation statements)
references
References 15 publications
5
32
0
1
Order By: Relevance
“…In addition, a higher ethnic identity was found to be associated with lower body dissatisfaction. This pattern is consistent with theoretical views about the protective nature of ethnic identity (Croll et al, 2002), but not consistent with studies that did not find such a link (Iyer & Haslam, 2003;Phan & Tylka, 2006). However, different body image measures were used across studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, a higher ethnic identity was found to be associated with lower body dissatisfaction. This pattern is consistent with theoretical views about the protective nature of ethnic identity (Croll et al, 2002), but not consistent with studies that did not find such a link (Iyer & Haslam, 2003;Phan & Tylka, 2006). However, different body image measures were used across studies.…”
Section: Discussionsupporting
confidence: 88%
“…With regard to racial/ethnic teasing, consistent with previous research (Iyer & Haslam, 2003;Reddy & Crowther, 2007), a history of racial/ethnic teasing was associated with lower self-esteem, greater endorsement of media beauty ideals, more body dissatisfaction, and higher levels of disordered eating. However, when mediators were considered, the structural model indicated racial/ethnic teasing only had significant direct effects on media internalization.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For racial minorities, who possess phenotypic features that don't conform to this ideal, adherence to the White ideal can be damaging (Cheng, 2014;Iyer & Haslam, 2003;Reddy & Crowther, 2007). The present studies found evidence for an actual-ideal discrepancy in how racial minorities perceived themselves, phenotypically.…”
Section: Discussionmentioning
confidence: 46%
“…Supporting this notion, experiences of racial teasing and perceived racial discrimination are associated with racial minorities' internalization of general media standards of beauty (Cheng, 2014), and body dissatisfaction (Iyer & Haslam, 2003;Reddy & Crowther, 2007).…”
Section: Shifting Actuals and Idealsmentioning
confidence: 90%